2018
DOI: 10.1002/2017ja024888
|View full text |Cite
|
Sign up to set email alerts
|

Global Characteristics of Electromagnetic Ion Cyclotron Waves Deduced From Swarm Satellites

Abstract: It is well known that electromagnetic ion cyclotron (EMIC) waves play an important role in controlling particle dynamics inside the Earth's magnetosphere, especially in the outer radiation belt. In order to understand the results of wave‐particle interactions due to EMIC waves, it is important to know how the waves are distributed and what features they have. In this paper, we present some statistical analyses on the spatial distribution of EMIC waves in the low Earth orbit by using Swarm satellites from Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 52 publications
5
45
5
Order By: Relevance
“…The prenoon sector (10:00–12:00 MLT) shows higher occurrence rate than the afternoon sector (12:00–14:00 MLT). The local time distribution of the occurrence rate of storm time EMIC waves are different from those of statistical results by H. Kim et al () based on Swarm wave events from December 2013 to June 2017. In their work quite comparable occurrence distribution was found around the noon and midnight, while in the present work, we found maximum occurrence in the premidnight sector when compared to the prenoon, postnoon, and postmidnight sectors.…”
Section: Observationscontrasting
confidence: 89%
See 2 more Smart Citations
“…The prenoon sector (10:00–12:00 MLT) shows higher occurrence rate than the afternoon sector (12:00–14:00 MLT). The local time distribution of the occurrence rate of storm time EMIC waves are different from those of statistical results by H. Kim et al () based on Swarm wave events from December 2013 to June 2017. In their work quite comparable occurrence distribution was found around the noon and midnight, while in the present work, we found maximum occurrence in the premidnight sector when compared to the prenoon, postnoon, and postmidnight sectors.…”
Section: Observationscontrasting
confidence: 89%
“…Kim et al, ; Park et al, ), Combined Release and Radiation Effects Satellite (CRRES; e.g., Halford et al, ; Min et al, ; Meredith et al, ), Dynamic Explorer 1 (Erlandson & Ukhorskiy, ), Van Allen Probes (VAPs; Saikin et al, ; D. Wang et al, ; Yu et al, ), and Magenetospheric Multiscale mission (X. Y. Wang et al, ). Ionospheric EMIC waves have been statistically studied using data from the Magnetic Field Satellite, Freja, Dynamic Explorer 2, Challenging Minisatellite Payload, and Swarm satellites (e.g., Erlandson & Anderson, ; Iyemori & Hayashi, ; H. Kim et al, ; Mursula et al, ; Park et al, ). These studies found that the source regions of EMIC waves varied over a wide range of magnetic local times (MLTs) from 03:00 to 20:00 MLT and over the L shells from 2 to 13 R E , which correspond to the range of invariant latitudes (ILat) from 45° (midlatitudes) to 74° (auroral zone).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic ion cyclotron (EMIC) waves are in the typical frequency range of 0.1-5 Hz that correspond to Pc1 pulsations on the ground. Generally, in the magnetosphere, EMIC waves can be excited by the cyclotron instability of hot ions (1-100 keV) with temperature anisotropy (T ⊥ > T // ) near the Earth's magnetic equator -particularly, in the region with a large plasma density and weak magnetic field, such as the plasmapause, ring current, and plasma sheet (Cornwall et al, 1965;Erlandson et al, 1993;Horne and Thorne, 1993;Anderson et al, 1996;Lin et al, 2014). Previous studies indicate that hot ion temperature anisotropy (T ⊥ > T // ) near the Earth's magnetic equator can be caused by several possible mechanisms, such as plasmapause expanding into the ring current region during the storm recovery phase (Cornwall et al, 1970;Russell and Thorne, 1970), mid-energy ions penetrating into the ring current region from the plasma sheet (Bossen et al, 1976), the solar wind dynamic pressure enhancement, or the magnetosphere compression (Olson and Lee, 1983;Anderson and Hamilton, 1993;McCollough et al, 2010;Usanova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the Earth's radiation belt, much attention is paid on low‐frequency electromagnetic (EM) waves, including ultralow frequency waves, whistler‐mode chorus, plasmaspheric hiss, EM ion cyclotron, and magnetosonic waves. The reason is that these waves are known to play important roles as acceleration and loss mechanisms for electrons in the relativistic energy range (Bortnik & Thorne, , ; Claudepierre et al, ; Hwang et al, ; Kim et al, ; Li et al, ; Meredith et al, ; Ni et al, ; Nishimura et al, ; Santolík et al, ; Summers et al, ; Thorne et al, , ; Ukhorskiy et al, ). The occurrences of these low‐frequency waves are, however, not pervasive, and their excitations are highly correlated with geomagnetic activity levels.…”
Section: Introductionmentioning
confidence: 99%